İlköğretim 5. sınıf fen bilgisi öğretiminde yararlanılan kalite araçlarının tam öğrenmeye etkisi - Tüysüz, Burçak (My University, 2004)
PERCEIVED IMAGE OF POLICE AND AN APPLICATION : TRAFFIC POLICE OF ISTANBUL AS AN EXAMPLE In order to make an efficient practice on the goals of the companies and organizations, relations with their aimed group of public is possible only by using the dependable and clear means of communication, which needs to have a powerful Public Relations (PR) network. Exhibitions, annuals, billboards, letters, brochures can be counted in PR efforts of companies and organizations however this study refers only to the image concept, that maybe summarized as the character of a company. If the goals and purposes of the companies match each other, then their perceived image will be more understandable. It is also known that the image has significancy to get the support of the public. In this aspect, perceived image of traffic police which is a unit in Public Security Organization, is evaluated. We limited our practice with Composing and Controlling Unit of Traffic Police because they are the ones who contact public in the streets and therefore the results will have more objective reflections. A questionnaire was also applied to the residents of Sefaköy and Yeşilköy at random, and the questions were evaluated by SPSS procedure that based on demographic factors such as district, education, age, income etc. It is revealed that conceived image of Traffic Police in both district is not so good. As a result, every member of this unit must increase their performance by fulfilling their duties and responsibilities staying in the frame of law.
Keywords: Bilim; Eğitim; Eğitim Araçları; Fen Bilgisi_Öğrenim ve Öğretim; İlk öğretim; İlkokul konuları; sağlık; teknoloji